The Role of Green Accounting and CSR in Driving Sustainable Development: Evidence from Indonesia’s Mining Industry - Gilang de Breving; Irfan Zamzam; Kasim Sinen; Zainuddin Zainuddin (Information Technology and Science (ITScience), 2025)
This study addresses the environmental challenges posed by mining industry activities, which threaten the achievement of sustainable development goals. The primary objective is to examine the effect of green accounting and corporate social responsibility (CSR) on sustainable development. Utilizing a quantitative approach, the study employs multiple linear regression analysis with the assistance of SmartPLS 4. The sample comprises mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, selected using a purposive sampling method. The novelty of this research lies in its exclusive focus on green accounting and CSR as independent variables—excluding variables such as material flow cost accounting—and its specific emphasis on the mining sector, whereas most previous studies focused on other industrial sectors. The findings reveal that both green accounting and CSR have a positive and significant influence on sustainable development. This suggests that companies integrating environmental and social considerations into their business practices are more likely to enhance their long-term sustainability. The study concludes that green accounting and CSR serve as strategic tools in promoting responsible business conduct and securing stakeholder legitimacy. Future research is recommended to explore additional variables that may contribute to sustainable development and to expand the scope to other industry sectors, thereby enriching empirical insights in the field of sustainability accounting